2021
DOI: 10.2147/ccid.s305976
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic Delusions: An Investigation into the Role of Rapid Visual Adaptation in Aesthetic Practice

Abstract: Background To date, the process of adaptation in the setting of aesthetic medicine has not been investigated. The combination of complex advanced feedback in the current intense social media milieu, in conjunction with easily accessible and effective aesthetic treatments, has produced pockets of overtreated patients and over-zealous practitioners. We examine whether aesthetic assessments of attractiveness and what appears natural can be distorted by the cognitive process of adaptation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…However, they can then quickly adapt their attitudes and, probably, their taste. Indeed, similar effects were found regarding aesthetic appreciation, for instance, with employed material such as lip attractiveness after adaptation to lip fullness [42] or face attractiveness in photographs and art portraits [43].…”
Section: Short-term Change Of Likingsupporting
confidence: 54%
“…However, they can then quickly adapt their attitudes and, probably, their taste. Indeed, similar effects were found regarding aesthetic appreciation, for instance, with employed material such as lip attractiveness after adaptation to lip fullness [42] or face attractiveness in photographs and art portraits [43].…”
Section: Short-term Change Of Likingsupporting
confidence: 54%
“…4 Emerging dermatologic evidence and anecdotal experience suggests that repeated rapid imagery exposures, as would be seen in Instagram, may be able to retrain our brains to redefine what we perceive as attractive through visual adaptation . 5 Now, after short exposures to exaggerated facial features (e.g., overfilled lips, overly chiseled jawlines), our patients may actually unconsciously recalibrate their brains. After exposure, they might appreciate unnatural imagery as more attractive than their previous preferences and what is anatomically within the range of normal.…”
mentioning
confidence: 89%
“…This malleability of visual systems, known as visual facial adaptation, has been investigated in a recent study by Goldie et al 22 The study demonstrated how the perception of attractiveness of different lip sizes may be shifted by an average of 20% toward larger lips after a short exposure of a face with very large lips. 22 This temporary but long-lasting visual adaptation is a subconscious process which can lead to more extreme provider bias where sub-groups can become over-treated and their parameters of attractiveness are inaccessible to the population as a whole.…”
mentioning
confidence: 99%
“…The malleability of the visual systems, which normally helps us to adapt and appreciate the local aesthetic norms also presents a potential for error in aesthetic practice as technological image manipulation or emersion among over‐treated faces can create a skewed and extreme visual diet which can profoundly effect the practitioners’ ability to achieve natural and beautiful outcomes. This malleability of visual systems, known as visual facial adaptation, has been investigated in a recent study by Goldie et al 22 The study demonstrated how the perception of attractiveness of different lip sizes may be shifted by an average of 20% toward larger lips after a short exposure of a face with very large lips 22 . This temporary but long‐lasting visual adaptation is a subconscious process which can lead to more extreme provider bias where sub‐groups can become over‐treated and their parameters of attractiveness are inaccessible to the population as a whole.…”
mentioning
confidence: 99%